Analisis dan Rekayasa Proses Produksi untuk Mengendalikan Environmental Impact Menggunakan Metode LCA - Bagaswara, Moch. Esa Adin; Hadi, Yuswono (Metris: Jurnal Sains dan Teknologi, 2017)
MAY'S BAKERY is a SME engaged in the field of food. Small business scale makes this SME having less attention to the potential of environmental impact, especially that can be caused in the production process. The purpose of this research is to assess and control the environmental impact of bread production process, so that the researcher can design the proposal of alternative production process to choose the which one is the better process. This assessment and control is done by using the Life Cycle Assessment (LCA) method. Assessment using LCA is done with the help if SimaPro software. Based on the analysis results, it is known that the environmental impact value caused by the production process currently applied by SME is 3.3824536 Pt and the environmental impact value caused by the alternative production process scenario that can be applied at SME is 3.74539 Pt. So based on the environmental standpoint and LCA, the production process that currently applied at SME is better than the alternative production process scenario.